2000
DOI: 10.1021/bi9925524
|View full text |Cite
|
Sign up to set email alerts
|

The 1.9 Å Resolution Crystal Structure of Phosphono-CheY, an Analogue of the Active Form of the Response Regulator, CheY,

Abstract: To structurally characterize the activated state of the transiently phosphorylated signal transduction protein CheY, we have constructed an alpha-thiophosphonate derivative of the CheY D57C point mutant and determined its three-dimensional structure at 1.85 A resolution. We have also characterized this analogue with high-resolution NMR and studied its binding to a peptide derived from FliM, CheY's target component of the flagellar motor. The chemically modified derivative, phosphono-CheY, exhibits many of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
63
1
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 32 publications
5
63
1
2
Order By: Relevance
“…Similar interactions have been reported for many structures of the activated regulatory domains, such as of Spo0A, 45 FixJ 46 and CheY. 47,48 The area that differs most between the two structures is the β4-α4 loop, specifically residues Thr81, Gly82 and Arg83 ( Fig. 2(a)).…”
Section: Coordination At the Active Site And Differences In The Two Ssupporting
confidence: 79%
“…Similar interactions have been reported for many structures of the activated regulatory domains, such as of Spo0A, 45 FixJ 46 and CheY. 47,48 The area that differs most between the two structures is the β4-α4 loop, specifically residues Thr81, Gly82 and Arg83 ( Fig. 2(a)).…”
Section: Coordination At the Active Site And Differences In The Two Ssupporting
confidence: 79%
“…Previous genetic and nuclear magnetic resonance studies have indicated that it is the ␣4-␤5-␣5 face of CheY that binds to its target protein, FilM (4). When high-resolution structures of active and inactive CheY were compared, a conserved residue in this face, CheY Tyr106, was found to flip between a solvent-exposed inactive conformation and a buried active conformation (9). Similar conformation changes of the conserved Tyr (or Phe) were observed in other receiver domain structures (28).…”
Section: Discussionmentioning
confidence: 62%